A Systematic Review of Histone Lysine‐Specific Demethylase 1 and Its Inhibitors. Issue 5 (19th May 2015) - Zheng, Yi‐Chao; Ma, Jinlian; Wang, Zhiru; Li, Jinfeng; Jiang, Bailing; Zhou, Wenjuan; Shi, Xiaojing; Wang, Xixin; Zhao, Wen; Liu, Hong‐Min
Abstract Histone lysine‐specific demethylase 1 (LSD1) is the first discovered and reported histone demethylase by Dr. Shi Yang's group in 2004. It is classified as a member of amine oxidase superfamily, the common feature of which is using the flavin adenine dinucleotide (FAD) as its cofactor. Since it is located in cell nucleus and acts as a histone methylation eraser, LSD1 specifically removes mono‐ or dimethylated histone H3 lysine 4 (H3K4) and H3 lysine 9 (H3K9) through formaldehyde‐generating oxidation. It has been indicated that LSD1 and its downstream targets are involved in a wide range of biological courses, including embryonic development and tumor‐cell growth and metastasis. LSD1 has been reported to be overexpressed in variety of tumors. Inactivating LSD1 or downregulating its expression inhibits cancer‐cell development. LSD1 targeting inhibitors may represent a new insight in anticancer drug discovery. This review summarizes recent studies about LSD1 and mainly focuses on the basic physiological function of LSD1 and its involved mechanisms in pathophysiologic conditions, as well as the development of LSD1 inhibitors as potential anticancer therapeutic agents.